THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND INTELLECTUAL INTELLIGENCE ON THE QUALITY OF PARAWISATA HUMAN RESOURCES IN PANGANDARAN BEACH TOURISM OBJECT - Arga - Sutrisna; Depy Muhamad Pauzy (JOBS (Jurnal Of Business Studies), 2019)
This research is one of the efforts of researchers to develop tourism human resources in Pangandaran beach tourism, the development of tourism human resources in Pangandaran attractions is very important to face the MEA (ASEAN Economic Community), it is hoped that with good tourism human resources can produce resources very large regional income. the purpose of this study is first to find out the intellectual intelligence, emotional intelligence, and the quality of human tourism resources in Pangandaran beach tourism objects, secondly to know the effect of intellectual intelligence and emotional intelligence simultaneously on the quality of tourism human resources in Pangandaran beach tourism objects, the third to know the effect of intellectual intelligence and emotional intelligence partially on the quality of tourism human resources in Pangandaran beach tourism objects, and the fourth becomes the basis of subsequent research. The method used to achieve the above objectives is an explanatory research method, the use of this method because researchers not only describe the empirical facts found in the field, but also intend to analyze and explain the influence between variables. This research was conducted on tourism human resources in Pangandaran beach tourism objects with a sampling system. The results of this study that the variable of emotional intelligence significantly influence the quality of tourism human resources and that the intellectual intelligence variable significantly influences the quality of tourism human resources and emotional intelligence and intellectual intelligence simultaneously significantly influence the quality of tourism human resources